Civil society perspectives on green jobs in sustainable energy: The case of European Malta. Issue 5 (August 2019) - Briguglio, Michael; Brown, Maria
The objective of this paper is to analyse the perspectives of civil society actors in Malta about the country's sustainable energy policy and its impact on green jobs. Perspectives of 11 civil society actors comprising employers, trade unions and non-governmental organisations are analysed to provide a broad reflexive analysis of the policy process in question. Findings illuminate a broad consensus within civil society that the policymaking process in the field of sustainable energy should incorporate different voices from civil society – such as employers, trade unions and environmental non-governmental organisations – apart from experts in energy, economics and other areas. Indeed, this study's findings include civil society's reviews on how commercial viability, workers' rights, environmental protection and sustainability interact with and within the sustainable energy sector and related green jobs. Nonetheless, this study signals that within Maltese civil society, sharing of knowledge and good practice and effort coordination lack. Different interests and sectarianism testify to inconsistently interacting and competing human local networks. This broadens the discourse on effective sustainable energy policy and creation of related green jobs, also making it more complex. Indeed, the direction of such discourse bears potential for sporadic development. Whilst challenging vertical trajectories, institutionally centred and technical transitions in the area of environmental sustainability, the primary data gained from this study highlight need for policy to address the identified challenges through projects, funding and incentives that foster coordination between different types of civil society organisations.